Acephate exposure during a perinatal life program to type 2 diabetes. (30th November 2016) - Ribeiro, Tatiane Aparecida; Prates, Kelly Valério; Pavanello, Audrei; Malta, Ananda; Tófolo, Laize Peron; Martins, Isabela Peixoto; Oliveira, Júlio Cezar de; Miranda, Rosiane Aparecida; Gomes, Rodrigo Mello; Vieira, Elaine; Franco, Claudinéia Conationi da Silva; Barella, Luiz Felipe; et al.
Abstract: Acephate has been used extensively as an insecticide in agriculture. Its downstream sequelae are associated with hyperglycemia, lipid metabolism dysfunction, DNA damage, and cancer, which are rapidly growing epidemics and which lead to increased morbidity and mortality rates and soaring health-care costs. Developing interventions will require a comprehensive understanding of which excess insecticides during perinatal life can cause insulin resistance and type 2 diabetes. A Wistar rat animal model suggests that acephate exposure during pregnancy and lactation causes alterations in maternal glucose metabolism and programs the offspring to be susceptible to type 2 diabetes at adulthood. Therapeutic approaches based on preventive actions to food contaminated with insecticides during pregnancy and lactation could prevent new cases of type 2 diabetes.